Quantity Surveyors’ Response to the COVID-19 Outbreak: A Mixed Method Approach - Seng Hansen; Susy F Rostiyanti; Rizaldi Rizaldi; Clara Andjarwati (Journal of the Civil Engineering Forum, 2021)
The COVID-19 outbreak began at the end of 2019, and has evolved to a pandemic threatening various industries’ sustainability. Decisive actions have been taken to tackle the pandemic’s spread, however, various impacts continue to be felt by many industries, including the construction industry. This paper therefore focuses on the COVID-19 outbreak’s impact on Quantity Surveyors’ (QS) construction projects and activities, as a key profession in the industry. A mixed method approach, questionnaire survey followed by expert interviews, was adopted. Subsequently, 199 valid responses for analysis were obtained from the questionnaire distribution, using descriptive statistics and Significance Index. Furthermore, qualitative data were acquired through semi-structured interviews with five experts, and analyzed using a structured thematic analysis. According to the results, 56.78% of respondents experienced project slowdowns, 13.57% experienced project suspensions or terminations, and 12.56% experienced cost overruns. Most respondents acknowledged the pandemic had present changes to projects (84.92%), in the form of changes in organization structure, work culture, technological application, and project objectives. Meanwhile, the Significance Index has successfully established an 11-factors ranking, regarding the pandemic’s impact on QS activities, with impact on the overall project completion as the most profound impact followed by impacts on project scheduling, supply chain, tendering, cost controlling, and claim management. This study’s qualitative and quantitative findings tend to be in accordance, thus, providing some fundamental insights regarding the COVID-19 outbreak’s impact on the construction industry, including direct impacts on project sustainability, technology adoption, and project resiliency issues. In addition, this study also contributes to scientific knowledge by discussing the issues and trends of work culture changes in QS professional activities.